Investigating the Early Bronze Age II settlement at Hacılar Büyük Höyük (Burdur, Türkiye) - Gülsün Umurtak (Българско е-Списание за Археология, 2025)
After the EBA I period came to an end at Hacılar Büyük Höyük around 2800 BC, the EBA II period can be easily followed in the excavations carried out at Kuruçay and Bademağacı Höyük, and in the neighbouring regions to the south, west, north and east of the Burdur – Antalya Region. Architectural remains from this period at Hacılar Büyük Höyük were uncovered in Trenches AB and C. Although the structures were badly damaged due to their proximity to the surface, the pottery and other finds that were obtained provide very interesting insights. The pottery uncovered so far includes a very diverse repertoire of forms that can be divided into five ware groups. In the same period, numerous fired clay finds such as schematic figurines that are slightly different from each other, stamp seals, schematic figurine-seals, numerical tablets and labels have been uncovered. In addition to these, metal finds such as an iron dagger with a wooden handle and traces of cotton weaving on it, and a gold earplug provide valuable information and insights into the unique cultural, social and economic dimensions of the settlement. All these finds show that Hacılar Büyük Höyük was a dominant centre in the EBA II period, as it was during EBA I.